Historicity of the Qur'an and Hadith: Historical Dynamics and Effects - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Universitas Hamzanwadi, 2023)
The paper discusses the foundational role of al-Quran and Prophetic narrations (al-hadith) in Islamic intellectual history and its religious tradition. It looks into the cultural impact of its moral-spiritual teaching and its historical significance in developing and fulfilling its fundamental role and social obligation in delivering and justifying the principal ideal of morality and fairness, contributing to medieval civilization and the formation of higher ethical-legal framework, and its state-of-the-art manifestation as set forth in the tafsir of Risalah al-Nur by Said Nursi. The study is based on library research using historical and qualitative approaches and documentation technique. The finding shows that the position of al-Quran and hadith was vital in informing and shaping the historical concept and understanding and paradigm of tawhid and in reinforcing the religious belief and practice and spiritual consciousness of the ummah. In the context of modern commentary, its philosophical ideas and interpretation were brought forth by Said Nursi in Risalah al-Nur that contextualize its discursive history and outline its religious and scientific significance and transcendental values and its role in the current debates of the philosophy of science, revelation, and scripture.Artikel ini mengulas historisitas Alquran dan hadis serta perannya dalam sejarah Islam dan tradisi intelektual. Ia melihat kesan historis dan dinamika ajaran moral dan spiritualnya dalam menafsirkan pandangannya tentang nilai moralitas dan aspek sosio-historisnya, serta kontribusinya terhadap perkembangan sejarah peradaban, pembentukan hukum, dan manifestasi akliahnya yang dirumuskan dalam buku tafsir Risalah al-Nur oleh Said Nursi. Penelitian ini bersifat kualitatif dengan menerapkan metode kajian sejarah yang bersifat dokumentasi dan analisis isi. Hasil penelitian menunjukkan keunggulan fungsi Alquran dan Hadis dalam membentuk pemahaman dasar sejarah tentang moral dan nilai-nilai moral serta pengaruhnya dalam memperkuat keyakinan tauhid dan psikologi keagamaan umat. Dalam konteks penafsiran dan signifikansi historisnya, wacana ini disajikan dalam buku Risalah al-Nur karya Said Nursi yang membahas pandangan hidup Alquran dan Hadis serta kesannya dalam membingkai pemahaman wahyu dan sejarahnya dalam konteks pemikiran filosofis dan hukum ilmiah.